Mothers' utilization and associated factors in preconception care in northern Ethiopia: a community based cross sectional study - Tsrity Tadese Asresu; Desta Hailu; Berhe Girmay; Mulugeta Woldu Abrha; Haftom Gebrehiwot Weldearegay (BMC, 2019)
Abstract Background Adverse pregnancy outcomes remain a prevalent health problem in Ethiopia. Mothers' use of preconception care service has the potential to avert many of the adverse outcomes. However, the use of this service and its determinants is not well investigated. Therefore, this study was conducted to assess the utilization and determinants of preconception care among recently delivered mothers. Methods A community based cross-sectional design was conducted among 564 recently delivered mothers in Mekelle City, Northern Ethiopia. A multi stage cluster sampling technique was employed. Data was collected using a pre-tested, structured interviewer questionnaire and was entered in to Epi-Info™ Version 7 and analyzed using SPSS™ Version 20.0. Descriptive, bivariable and multivariable logistic regression was used to identify the association. Results This study revealed that, 102(18.2%) of the mothers had utilized preconception care. Mothers' knowledge on preconception care (AOR: 2.21; 95% CI: 1.03, 4.73), prior experience of adverse birth outcomes (AOR: 5.10; 95% CI: 2.31, 11.24), history of chronic health problems (AOR: 5.69; 95% CI: 2.06, 15.72), husband's support (AOR: 13.84; 95% CI: 6.02, 31.79), and challenges in accessing a health facility (AOR: 0.24; 95% CI: 0.16, 0.48) were significantly associated with preconception care service utilization. Conclusion Mothers' utilization of preconception care is low. Mothers knowledge on preconception care, experience of adverse birth outcome, having chronic health problems and husband support increases utilization of preconception care. However, mothers who experienced challenges in visiting a health facility showed decrease preconception care utilization. Therefore, increased efforts are need in terms of advocating for involvement of husband's and awareness creation respecting preconception care services for all women.